The Alteration Visual Field Defect in Ischemic Stroke Patients After Three Months Therapy - Frida Lestari; Devi Azri Wahyuni (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2016)
Background: Ischemic stroke are lack of blood flow to the brain and it could influence the visual field. Approximately more than half of the ischemic stroke patient have visual defect.Objective : Disturbance of blood flow on visual pathway have impact to the visual field defect. In stroke ischemic patient, recirculation of penumbra at the brain on the third months after onset can rehabilitate the visual pathway, also it will improve the outcome of visual filed defect. So it could be initial detection for rehabiltation of visual field defect.Methods: This study was intended to compere visual field defect of ischemic stroke patient after three months therapy conducted form September 2014 - February 2015 in Mohammad Hoesin General Hospital Palembang. A total of 12 patients who met the inclusion criteria were recruited by consecutive sampling. All patients were endure based on ophthalmology and visual field examination using Humphrey Field Analyzer twice. First after relieving from the attack of stroke and second after three months therapy. Measurement of standard have to compare the value of MD, VFI, PSD, PD and pattern visual field defect. Results: There were significant difference in value of MD, VFI, PSD and PD<0,5% for both eyes on stroke ischemic patients after three months therapy. Almost all variable value were increasing to improvement of defect. The most common type of visual field defect is homonymous hemianopia. Conclusion: There were improvement in visual field defect in patients with stroke ischemic after three months therapy. Keywords: Ischemic stroke, visual field defect, penumbra, recirculation of brain, Mean Deviation (MD), Visual Field Index (VFI), Pattern Standard Deviasion (PSD), Pattern Deviation (PD)